Comparison of Team-Based and Flipped Classroom Learning on Academic Achievements of Physical Therapy Students - Sana Umar, Amna Zia, Maham Khalid, Faiqa Mehmood Rana, Saima Jabbar (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: In this study, the post-implementation effects of two active learning strategies i.e., team-based learning (TBL) and flipped classroom learning (FCL) on academic achievements in terms of test scores were compared in undergraduate physical therapy students. Methods: This was a quasi-experimental study. Fifty undergraduate physical therapy students were included in this study. Students were equally divided into two groups i.e., team-based learning (TBL) and flipped classroom learning (FCL). The perception of students about this mode of learning was assessed by using the Likert scale. To assess post-implementation performance multiple choice question (MCQ) based test was used. Results: The average age of students in TBL group was 19.12±0.60 years whereas, in the FCL group average age was 19.04±0.45 years. 52% of students of the TBL group and 56% of students of the FCL group preferred the implemented active learning strategies as a better learning mode as compared to the conventional method. Both learning strategies i.e., FCL and TBL increased the post-knowledge level of students (p-value <0.05 for both). But while comparing FCL and TBL, the post-knowledge level in TBL was68.88±7.08 and in FCL group was 79.48±10.02 with p<0.05 showing that FCL was better than TBL. Conclusion: Team-based and flipped class room learning increased the knowledge level of students. As compared to team-based learning, flipped class room learning was a better learning strategy. Keywords: students learning, academic, learning in classroom, Team based classroom learning, flipped classroom learning